Multiculturalism and Conflict Reconciliation in the Asia-Pacific : Migration, Language and Politics. - Shimizu, K.; Bradley, W. (London : Palgrave Macmillan UK, 2014)
This book is open access under a CC BY license. This edited collection focuses on theories, language and migration in relation to multiculturalism in Japan and the Asia-Pacific. Each chapter aims to provide alternative understandings to current conflicts that have arisen due to immigration and policies related to education, politics, language, work, citizenship and identity.
Cover -- Title Page -- Copyright Page -- Table of Contents -- List of Figures and Tables -- Foreword by Koichi Iwabuchi -- Acknowledgments -- Notes on Contributors -- 1 Introduction -- Part I Theories and Identities -- 2 Multicultural Coexistence in Japan: Follower, Innovator, or Reluctant Late Adopter? -- 3 A Critical Analysis of Multiculturalism and Deviant Identities: Untold Stories of Japanese Americans without Nations -- 4 Theorizing Multiculturalism: Modeling the Dynamics of Inclusion and Exclusion in School-Based Multicultural Settings -- Part II Language and Language Policies -- 5 Who Owns Our Tongue? English, Academic Life, and Subjectivity -- 6 Preservice and Inservice English as a Foreign Language Teachers' Perceptions of the New Language Education Policy Regarding the Teaching of Classes in English at Japanese Senior High Schools -- 7 An Alternative Approach to Foreign LanguageEducation in Japan with a View toward Becominga Multicultural Society -- Part III Migration and Citizenship -- 8 Female Domestic Workers on the Move: Examining Global Householding and Global De-Householding in Today's World -- 9 Multiculturalism Policies and the Stepwise International Migration of Filipino Nurses: Implications for Japan -- 10 Who Benefits from Dual Citizenship? The New Nationality Law and Multicultural Future of South Korea -- 11 "Global Jinzai," Japanese Higher Education, and the Path to Multiculturalism: Imperative, Imposter, or Immature? -- Afterword -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books